A cautionary tale: A study of a methane enhancement over the North Sea. Issue 14 (19th July 2017) - Cain, M.; Warwick, N. J.; Fisher, R. E.; Lowry, D.; Lanoisellé, M.; Nisbet, E. G.; France, J.; Pitt, J.; O'Shea, S.; Bower, K. N.; Allen, G.; Illingworth, S.; et al.
Abstract: Airborne measurements of a methane (CH4 ) plume over the North Sea from August 2013 are analyzed. The plume was only observed downwind of circumnavigated gas fields, and three methods are used to determine its source. First, a mass balance calculation assuming a gas field source gives a CH4 emission rate between 2.5 ± 0.8×10 4 and 4.6 ± 1.5×10 4  kg h −1 . This would be greater than the industry's reported 0.5% leak rate if it were emitting for more than half the time. Second, annual average UK CH4 emissions are combined with an atmospheric dispersion model to create pseudo‐observations. Clean air from the North Atlantic passed over mainland UK, picking up anthropogenic emissions. To best explain the observed plume using pseudo‐observations, an additional North Sea source from the gas rigs area is added. Third, the δ 13 C‐CH4 from the plume is shown to be −53‰, which is lighter than fossil gas but heavier than the UK average emission. We conclude that either an additional small‐area mainland source is needed, combined with temporal variability in emission or transport in small‐scale meteorological features. Alternatively, a combination of additional sources that are at least 75% from the mainland (−58‰) and up to 25% from the North Sea gas rigs area (−32‰) would explain the measurements. Had the isotopic analysis not been performed, the likely conclusion would have been of a gas field source of CH4 . This demonstrates the limitation of analyzing mole fractions alone, as the simplest explanation is rejected based on analysis of isotopic data. Plain Language Summary: In the study, we have analyzed aircraft data to try and identify the source of a plume of methane observed over the North Sea. The flight circuited North Sea gas fields with the aim of intercepting any fugitive methane. Initial analysis of the amount of methane present and its location suggested that the methane was being emitted from the gas field area, and this was supported by dispersion modeling of the case. However, analysis of carbon isotopes in methane revealed that fugitive gas could not have been the primary component of the plume. As methane is often measured without analysis of its carbon isotopes, the authors feel that this is an important cautionary tale. We present our analysis of this case study with recommendations for how best to conduct such analyses in the future to try and avoid potential misdiagnosis of methane plume sources. Key Points: Three methods are used to analyze a methane plume observed over the North Sea Only with use of all three methods can the source of the plume be understood Measurement of carbon isotopes is essential for source identification, given limitations to the model and the extent of the measurements